Corporate Social Responsibility and Company Performance: Study in Companies Listed in Jakarta Islamic Index - Y Anni Aryani; Doddy Setiawan (Faculty of Economics and Business Udayana University, 2020)
This research aims at examining the effect of corporate social responsibility on firm performance. Sample of the study consists of company that listed on Jakarta Islamic Index during 2013-2015. This study uses multiple regression to test the hypothesis. The result shows that corporate social responsibility has positive effect on firm performance. The higher performance of corporate social responsibility, the better firm performance. Therefore, corporate social responsibility are able to drive firm performance better. Further, the study investigates in more deeply the effect of corporaqate social responsibility on the firm size and leverage. This provides similar result for each models. Thus, this study offers empirical evidence that corporate social responsibility has positive value to the firm performance.